The Role of Mesenchymal Stem Cells in Liver Regeneration - Hardian Gunardi (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Inflammation of the liver caused by cholestasis, viral infection, alcohol, autoimmune reactions, toxins, or metabolism will result in a prolonged immune response. As a result, simultaneous inflammation and tissue remodelling occur, resulting in fibrosis and eventually leading to cirrhosis. The main treatment for end-stage liver cirrhosis is liver transplantation. However, it is often not possible for patients to undergo this life-saving procedure. On the other hand, stem cell transplantation may be a potential strategy to prevent disease progression and improve the degree of fibrosis. Discussion: Inflammation of the liver activates hepatic stellate cells, which are perisinusoidal cells in the Disse cavity that contain vitamin A. Hepatic stellate cells activation results in retinoid storage loss and transformation into myofibroblast-like cells that express α-smooth muscle action (α-SMA) and produce collagen which plays a major role in fibrosis. Liver regeneration due to chronic liver damage is played by mesenchymal cells through the mesenchymal-epithelial or epithelial-mesenchymal transition (MET/EMT) process. Administration by the intrahepatic route is thought to be the ideal route because fewer cells are lost in the circulation and more mesenchymal stem cells differentiates into hepatocytes in the damaged liver area. However, intrasplenic route maybe an alternative with easier administration technique. There are special considerations regarding the risks, including the risk of carcinogenesis and viral transmission. Conclusion: Mesenchymal stem cells transplantation may be a potential therapeutic strategy for patients with end stage liver disease in the future. However, future research is needed regarding the risk of carcinogenesis and viral transmission following the procedure.